Personal search and well-founded suspicion: Perception of first instance criminal courts of the judiciary of Alagoas in 2023 - Silva, Weverton Luiz da (Research, Society and Development, 2024)
This research aims to present a study on the personal search procedure and the necessary founded suspicion as an instrument for promoting public safety. The research problem is to verify the perception of first instance criminal judges of the Judiciary of Alagoas regarding the characterization of founded suspicion in personal searches carried out by security agencies, which originated criminal proceedings in the year 2023. Regarding the technical procedures adopted, bibliographic, documentary and jurisprudential research was used. Regarding the objectives, this work can be defined as exploratory research. Regarding the approach to the problem, the research can be defined as quantitative, given the possibility of translating into numbers the number of decisions that analyzed and confirmed, judicially, the personal searches carried out by public security institutions under the allegation of founded suspicion. The scientific article also has an applied research nature, as it aims to generate knowledge aimed at providing a solution for possible abuses, in order to indicate the existing bodies and institutions with the power to monitor and hold accountable public agents who deviate from their conduct. After surveying the judicial decisions handed down, in 2023 alone, it was found that the characterization of well-founded suspicion was confirmed by the first instance magistrates of the Judiciary of Alagoas in 96.15% of the judicial statements analyzed.